Ansiedad y el rendimiento académico en los estudiantes de bachillerato de la unidad educativa Velasco Ibarra, cantón Guamote - Pilamunga Cepeda, María Gladys (2023)
ABSTRACT: The objective of this study was to determine the influence that exists between anxiety and academic performance in high school students of the Velasco Ibarra Educational Unit, Guamote canton. This is a study with a quantitative, non-experimental, cross-sectional and descriptive-correlational approach. The sample was defined by the intentional non-probabilistic type method, consisting of n= 190 high school students from the Velasco Ibarra Educational Unit, made up of 102 female and 88 male, aged between 15 and 16 years. The instruments used were the DASS 21 scale, which evaluated three subscales: depression, anxiety, and stress, and the report cards for the first semester of the 2022-2023 school year. It will be prolonged that there is a significant relationship between the variables, since only 8.4% of the population is at the normal level and for students with lower academic performance, they present high anxiety scores at the levels that show greater anxiety symptoms. the same When analyzing the subjects that present the greatest difficulty in terms of academic performance averages, it is evident in said group, Physics, English, Research, Language and Literature, Mathematics and Chemistry. Keywords: anxiety, stress, depression, academic performance, DASS-21, academic average.